RESPON MASYARAKAT TERHADAP PELAYANAN APARATUR KELURAHAN TAMPAN KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Sari, Asih Purnama; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The main duties and functions of the government apparatus are increasingly in the spotlight of the community because they get good services, the rights of the community, while the apparatus increase service participation, with basic principles of service that are simple, fast, precise, orderly, cheap, transparent and non-discriminatory. First, Society not only demands more efficient, and satisfying services, but also wants behavior that is more responsive and reflects propriety, ethical balance and wisdom. Second, The public is more critical in assessing the services provided by the government, especially at the village government level, something that become of the focus of the community with include public services or community services. However, This research is strived to find out how the comunity's response to the services provided by the village apparatus such as correspondence services and others, according to operational standards at the Tampan Payung Sekaki district office. In other words, The sample of this research is people who has job at the Tampan Payung Sekaki district office with total 77 person. Next, The researcher used quantitative descriptive methods and the data analyzed by using quantitatively and data instruments by using observation, questionnaires and documentation. Besides, From the research conducted, the reseracher found out that the community response to the service of urban village officials at the Tampan District Office of Payung Sekaki was good. Moreover, The response to the ability of the apparatus is 85.7% and the response to the service system is good or positive with a percentage of 66.0%. Keywords : Response, Service, Community